2004
DOI: 10.1111/j.1365-2672.2004.02222.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of 2,4,6-tribromophenol by bacterial cells attached to chalk collected from a contaminated aquifer

Abstract: Aim: To investigate the factors governing the adhesion and activity of the 2,4,6-tribromophenol (TBP) degrading bacterium Achromobacter piechaudii TBPZ-N61 on chalk from a contaminated aquifer. Methods and Results: Adhesion kinetics of TBPZ-N61 to grey and white chalk from a polluted fractured chalk aquifer was tested in a batch system. Both grey and white chalk contain ca 80% CaCO 3 , while grey chalk contains more organic matter (2AE4%) than the white chalk (0AE3%) and also contains Dolmite and Clinoptilolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…19) Cells adhering to chalk were more active in 2,4,6-TBP degradation than cells in suspension. 20) The bacterium, however, was not able to metabolize mono-or dibromophenols. 19,21) These results suggest that there are a number of bromophenoldegrading bacteria in various ecological niches, and that there is a diversity of dehalogenating enzymes with various substrate specificities.…”
Section: Discussionmentioning
confidence: 99%
“…19) Cells adhering to chalk were more active in 2,4,6-TBP degradation than cells in suspension. 20) The bacterium, however, was not able to metabolize mono-or dibromophenols. 19,21) These results suggest that there are a number of bromophenoldegrading bacteria in various ecological niches, and that there is a diversity of dehalogenating enzymes with various substrate specificities.…”
Section: Discussionmentioning
confidence: 99%
“…In this pH range, the surface is electrically neutral, whereas at higher or lower pH, the surface is negatively or positively charged, respectively (Somasundaran and Agar 1967). Previously, we demonstrated that the adhesion of Achromobacter piechaudii TBPZ‐N61 to chalk follows a Langmuir isotherm and at saturation, cells in the stationary growth phase adhere more efficiently to chalk particles than cells in the logarithmic phase (Nejidat et al. 2004).…”
Section: Introductionmentioning
confidence: 98%
“…1999). As a part of our effort to design a practical scheme for the remediation of contaminated fractured chalk aquifers, we have been studying bacterial cell adhesion kinetics on a chalk matrix and the activity of the adhered cells (Nejidat et al. 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported mixed trends of hydrophobicity between the logarithmic and stationary growth phases. Higher hydrophobicity was observed for stationary growth phase as compared to the logarithmic phase cultures in a number of past studies [36,51,54,69,70]. Opposite trend, i.e., hydrophobicity decrease with cell age was reported in some other studies [28,35,52,53,71].…”
Section: Effect On Hydrophobicitymentioning
confidence: 65%